Analisis Energy Efficiency Ratio (EER) pada AC Split yang Diretrofit dari Refrigeran R32 ke R290 dengan Massa Pengisian 40 Persen - Rizka Ulum; Gunawan Budi Santoso; Ngatmin; Susanto; Anang Anang Budhi Nugroho; M. Edi Pujianto (Universitas Muhammadiyah Metro, 2026)
The extensive use of split-air conditioning in tropical countries raises environmental concerns because of the high global warming potential of R32 refrigerant. The hydrocarbon refrigerant R290 offers a promising alternative with a very low gross pollutant content (less than 4) and a near-zero ozone depletion potential. However, its flammability and impact on performance at reduced charge densities require further investigation. This study assesses the energy efficiency ratio (EER) of 1 PK split AC retrofitted with 40% charge weight from R32 to R290. The experimental tests were carried out under five operating conditions with room temperature of 23-27 degrees Celsius and ambient temperature of 30-35 degrees Celsius. System parameters including pressures, temperatures, compressor power consumption and the flow rate of the refrigerant were measured. The software REPROP was used for the thermodynamic analysis and the EER calculation. The results show that R32 achieves a higher EER (24.59-26.35 Btu per kWh) than R290 (15.33-17.21 Btu per kWh), resulting in a reduction of efficiency of 30-45 percent. Although R290 showed lower power consumption (0.446-0.476 kW compared to 0.76-0.82 kW in R32), the reduced mass flow rate reduced the cooling capacity. The study concluded that the 40 percent R290 retrofit reduces energy consumption but compromises energy efficiency, which requires further research on optimised weight and system components.